( 6x – 5 ) ( 7x – 5 ) = … ?Note :Dah kletek” tangan v:​

Posted on

( 6x – 5 ) ( 7x – 5 ) = … ?Note :Dah kletek” tangan v:​

Penjelasan dengan langkah-langkah:

( 6x – 5 ) ( 7x – 5 )

= (6x×7x) – (6x×5) – (5×7x) + (5×5)

= 42x² – 30x – 35x + 25

= 42x² – 65x + 25

small{colorbox{black}{gray{boxed{{ sf:✨ color{f6fbff}{ḀṆṠẇḕṙ : ḃẏ}✨{ {pink{boxed{color{fdff28}{: - ꆰꍟꈤ꒒ - :}}}}}}}}}}

( 6x – 5 ) ( 7x – 5 )

= 6x(7x – 5) – 5(7x-5)

= 42x² – 30x – 35x + 25

= – 30x – 35x + 42x² + 25

= -65x + 42x² + 25